IDENTIFIKASI KUALITAS TANAH SAWAH DI DESA REROJA KECAMATAN MAGEPANDA KABUPATEN SIKKA - Bolly, Yovita Yasintha; Selfianus, Selfianus; Mutiara, Charly (Agriculture Faculty of Flores University, 2025)
Paddy fields with high agricultural activities greatly affect their quality. The purpose of this study was to determine the chemical properties and quality of paddy fields in Reroja Village. This study used an exploratory method. Soil samples were taken from paddy fields with three rice varieties, namely Inpari, Ciherang, and IR. The variables observed were soil pH, CEC, Organic C, Total N, Total P, Total K, and wet saturation. The criteria used in determining the location were paddy fields with an area of ??1 ha and cultivated rice varieties Ciherang, IR, and Inpari. The variables that had been analyzed were then determined for soil chemistry and soil quality criteria based on the Lowery scoring method. The results of the study showed that the pH of the rice field soil in Reroja Village was acidic with a pH value of 4.48 to 4.98, CEC was classified as high with a value range of 40.11 to 40.93, C-organic was classified as low with a value of 0.78 to 1.80, N-total was categorized as low with an inpari value of 0.08 to 0.15, P-available was categorized as medium and low with an inpari value of 30.10, 5.67 to 30.10, K-available was categorized as high with a value of 79.56 to 86.47, base saturation was categorized as high with a value of 87.90 to 88.11. The quality of the rice field soil in Reroja Village was said to be unhealthy, with a value of 1.7 to 2.0.